Analisis Strategi Pemasaran dalam Menghadapi Persaingan Bisnis Di Masapandemi di J&T Express Cabang Lubang Buaya Jakarta Timur - Megawati Megawati; Sugeng Santoso (Fakultas Ilmu Administrasi Universitas Krisnadwipayana Jakarta, 2022)
This study aims to identify and analyze marketing strategies in the face of business competition during the pandemic at J&T Lubang Buaya Branch, East Jakarta. This study uses a qualitative descriptive using interview, observation, and documentation data collection techniques conducted at J&T Express, Lubang Buaya Branch, East Jakarta. The informants in this study were employees and consumers of J&T Lubang Buaya Branch, East Jakarta. In this study using the 7P marketing strategy, namely Product, Price, Promotion, Place, People, Process, and Physical Evidence. The development of shipping goods in Indonesia is currently very fast. The existence of a pandemic has made the trend of online shopping increase in Indonesia. The marketing mix has seven elements that cannot be separated and are interrelated with each other. Keywords: Marketing Strategy, J&T Express, 7P Marketing Mix, Competition Business, Pandemic.